PENINGKATAN HASIL BELAJARA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE INVESTIGATION PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS X SMAN 10 - NINIK ASANAH (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
This research is a classroom action research that aims to improve the quality of learning outcomes of Indonesian language learning activities in student X through the Cooperative Type Group Investigation model at SMAN10 Luwu Utara, which is the purpose of the research. This study took a sample of class X-2 totaling 34 students consisting of 24 female students and 10 male students. The implementation of this study consisted of three cycles. Each cycle is carried out through the stages of planning, implementing actions, observing, reflecting and evaluating at the end of each cycle. I, cycle II, and cycle III. The data collection technique used is data collection through student activity observation sheets and learning outcomes tests, interviews and documentation. By using descriptive statistical analysis in the form of percentages and frequency tables, the results of this study show that the average increase in student learning outcomes has increased in the student learning process, namely 64.56% in the first cycle to 94.08% in the second and third cycles. Meanwhile, student activity in the first cycle reached 67.62%, increasing to 99.96% in the second and third cycles. From the results of the study it can be concluded that student learning outcomes increase through the Cooperative Model of Group Investigation Type, there is a tendency to increase student activity about the student learning process through the Cooperative Model of Group Investigation Type, as well as increase student activity and learning outcomes. ABSTRAKPenelitian ini adalah penelitian tindakan kelas yang bertujuan untuk meningkatkan kualitas aktivitas hasil belajar belajar Bahasa Indonesia pada siswa X melalui model Kooperatif Tipe Group Investigation pada SMAN10 Luwu Utara, merupakan tujuan dari penelitian. Penelitian ini mengambil sampel kelas X-2 berjumlah 34 orang siswa yang terdiri dari 24 siswa perempuan dan 10 siswa laki-laki pelakasanaan penelitian ini terdiri dari tiga siklus. Tiap siklus dilaksanakan melalui tahapan perencanaan, pelaksanaan tindakan, observasi, , refleksi dan evaluasi di setiap akhir ssiklus. I, siklus II, dan siklus III. Teknik pengumpulan data yang digunakan adalah pengumpulan data melalui lembar observasi aktivitas siswa dan tes hasil belajar., wawancara dan dokumentasi. Dengan menggunakan análisis statistik deskriptif berupa persentase dan tabel frekuensi hasil penelitian ini menunjukan peningkatan rata-rata hasil belajar siswa mengalami peningkatan pada proses belajar siswa yaiitu 64,56% pada siklus I menjadi 94,08% pada siklus II dan siklus III. Sedangkan aktivitas siswa pada siklus I mencapai 67,62% meningkat menjadi 99,96% siklus II dan siklus III. Dari hasil penelitian dapat disimpulkan bahwa hasil belajar siswa meningkat melalui Model Kooperatif Tipe Group Investigation, terdapat kecenderungan peningkatan aktivitas siswa tentang proses belajar siswa melalui Model Kooperatif Tipe Group Investigation, juga meningkatkan aktivitas dan hasil belajar siswa.